1982
DOI: 10.1152/ajpendo.1982.243.3.e182
|View full text |Cite
|
Sign up to set email alerts
|

Liver glycogen synthase and phosphorylase changes in vivo with hypoxia and anesthetics

Abstract: Methods for obtaining and processing rat liver for determination of glycogen phosphorylase a and synthase I activity were studied. An extremely rapid and profound increase in phosphorylase was induced by hypoxia. The effect on synthase I was slower and less striking. Using alpha- and beta-adrenergic antagonists, a catecholamine-depleting agent, and a ganglionic blocking agent, it was determined that adrenergic stimulation secondary to the surgical procedure required to obtain the liver was not a significant fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The anesthetic used has been shown not to result in activation of glycogen phosphorylase. An increase in the active form of phosphorylase has previously been shown to be an exquisitely sensitive indicator of hypoxemia and/or stress (14). We also have shown that the method used to procure liver samples, which were obtained while respiration and circulation were still intact, does not result in phosphorylase activation (14).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The anesthetic used has been shown not to result in activation of glycogen phosphorylase. An increase in the active form of phosphorylase has previously been shown to be an exquisitely sensitive indicator of hypoxemia and/or stress (14). We also have shown that the method used to procure liver samples, which were obtained while respiration and circulation were still intact, does not result in phosphorylase activation (14).…”
Section: Discussionmentioning
confidence: 72%
“…An increase in the active form of phosphorylase has previously been shown to be an exquisitely sensitive indicator of hypoxemia and/or stress (14). We also have shown that the method used to procure liver samples, which were obtained while respiration and circulation were still intact, does not result in phosphorylase activation (14). Two different methods of deproteinization were compared to ensure that deproteinization with an acid (HCIO 4 ) did not result in glycogenolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Phosphorylase a was increased in some, but not all, diabetic rats at 10-20 min after fructose gavage; this may have been due to stress from the gavage procedure (Table 2), because the phosphorylase a level has been shown to be exquisitely sensitive to stress. 20 In none of the animals was phosphorylase a decreased. By 60 min after fructose administration, phosphorylase a was unchanged from the control value.…”
Section: Diabetic Rats Normal Ratsmentioning
confidence: 94%
“…Within 10 s after the abdomen was opened, a section of liver was freeze-clamped in situ with a clamp developed in our laboratory for this purpose. 20 Liver samples were stored in liquid N 2 until analyzed later the same day. Animals were killed by removing the heart.…”
Section: Methodsmentioning
confidence: 99%